Tolerable level of corruption for foreign direct investment in Europe and Asia - Anselm Komla Abotsi (Contemporary Economics, 2018)
In 2009, Foreign Direct Investment (FDI) flows to developed countries experienced the largest decline among all regions and sub-regions. However, South, East and Southeast Asia showed the smallest decline among developing economies and remained the largest recipient of FDI inflows. Meanwhile, approximately 68% of the countries in Asia scored less than the tolerable level of corruption for investment (TLCI) in Africa (-0.27) over recent years. Moreover, corruption has been observed to be significant in virtually all Asian countries, but, despite this, the region remains the number one global investment destination. This study, therefore, estimates the TLCI in Asia and Europe to enable comparison across these regions. Secondary data from the World Development Indicators were used in this study. The frequency of the data is annual, and it is available from 1996 to 2013. The dynamic panel data estimation technique was deployed while controlling for other variables. The estimated TLCIs for Europe and Asia are 0.534 and -0.735, respectively, on the control of corruption scale, which ranges from approximately -2.5 (weak) to 2.5 (strong). Despite the lower TLCI in Asia, the region is still able to attract relatively more FDI inflow than Africa. This scenario may be attributed to the presence of sound policy factors that drive FDI inflows. Another reason may be due to the nature, scope, social role and the perception of corruption across these regions.
Keywords: F18; F23; F20; F30; 330; corruption; tolerable level of corruption for investment; foreign direct investment; institutions